Copper paste for forming sintered copper pillar, and method for producing bonded body

CN119588925APending Publication Date: 2025-03-11RESONAC CORP

Patent Information

Application Number
CN202411827311.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-09-25
Filing Date
2020-09-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

然而,在软钎焊中存在以下问题:(1)在焊料与电极焊盘之间及焊料与金属柱之间出现克氏空孔;(2)在接合后再次进行回焊工序时,焊料熔融而发生接合不良;(3)由于异种金属界面处的阻抗不匹配而产生信号的发射等

Benefits of technology

[0022] According to the present invention, it is an object to provide a method for producing a copper paste for forming a sintered copper column and a bonding body using the copper paste. When the copper paste for forming a copper column is placed for a long time, it is possible to stably form a bonding body bonded with a sintered copper column when the copper paste for sintering is mounted and sintered.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588925A_ABST
    Figure CN119588925A_ABST
Patent Text Reader

Abstract

The invention relates to a copper paste for forming a sintered copper pillar and a method for manufacturing a bonded body. A copper paste for forming a sintered copper pillar, which is used for forming a sintered copper pillar in which members are joined to each other, and which contains metal particles and an organic dispersion medium, the metal particles containing copper particles, and the organic dispersion medium containing 50-99% by mass of a high-boiling-point solvent having a boiling point of 280 DEG C or higher based on the total mass of the organic dispersion medium.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese application No. 202080067169.2, whose application date is September 18, 2020 and whose invention name is “Method for manufacturing copper paste and joint body for forming sintered copper pillars”. Technical Field

[0002] The present invention relates to a copper paste for forming a sintered copper column and a method for manufacturing a joint body. Background Art

[0003] Soldering is generally used for electrical bonding in electronic devices. For example, in flip-chip bonding of microdevices, solder balls or solder paste are used to bond the microdevice to electrode pads on a substrate.

[0004] In recent years, as the pitch of the terminals has become narrower, a method has been used in flip chip bonding to form metal pillars on micro devices and solder the metal pillars to electrode pads on a substrate. However, soldering has the following problems: (1) Kirschner voids occur between the solder and the electrode pads and between the solder and the metal pillars; (2) when the solder is reflowed after bonding, poor bonding occurs due to melting of the solder; and (3) signal transmission occurs due to impedance mismatch at the interface of dissimilar metals.

[0005] In view of this, a method of bonding using metals other than solder is being studied. For example, Patent Document 1 below proposes a method of bonding a copper column provided on a micro device to a copper pad on a substrate using a bonding agent (copper paste) mixed with copper microparticles and copper nanoparticles.

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: U.S. Patent Application Publication No. 2016 / 0351529 Summary of the invention

[0009] Technical issues to be solved by the invention

[0010] The method of Patent Document 1 has a problem that the copper pillars need to be formed in advance on the equipment, but the formation of the pillars takes time in the mainstream method of forming the copper pillars, that is, the formation method using electrolytic plating. In addition, if the plating speed is increased, the height deviation becomes larger, which is also a problem.

[0011] Therefore, the inventors of the present invention have studied a method in which a column precursor is formed between the bonding parts by using a copper paste containing copper particles and an organic dispersion medium and the column precursor is sintered, thereby forming a sintered copper column while bonding the bonding parts to each other. According to this method, a sintered copper column can be formed effectively and with high precision. However, the results of the research by the inventors of the present invention have found that when a long time (e.g., about 1 to 3 hours) is required from the formation of the column precursor to the mounting of the bonding part, there is a case where the bonding between the column and the bonding part is insufficient.

[0012] The present invention has been completed in view of the above situation, and its purpose is to provide a copper paste for forming a sintered copper column, and a method for manufacturing a joint body using the copper paste. The copper paste for forming a sintered copper column can stably form a joint body joined by a sintered copper column even when a joint component is mounted and sintered after a column precursor is placed for a long time.

[0013] Means for solving technical problems

[0014] One aspect of the present invention provides a copper paste for forming a sintered copper column, which is used to form a sintered copper column for bonding components to each other. The copper paste contains metal particles and an organic dispersion medium, the metal particles contain copper particles, and the organic dispersion medium contains 50 to 99 mass % of a high boiling point solvent with a boiling point of 280° C. or higher, based on the total mass of the organic dispersion medium.

[0015] According to the copper paste of the above aspect, even when the pillar precursor is left for a long time (for example, about 1 to 3 hours) and then the bonding member is mounted and sintered, a bonded body bonded by sintered copper pillars can be stably formed.

[0016] The content of the high boiling point solvent is preferably 5 to 30% by mass based on the total mass of the copper paste.

[0017] The organic dispersion medium may contain two or more high-boiling-point solvents.

[0018] The copper paste preferably contains at least one selected from the group consisting of isobornylcyclohexanol and butyl stearate as a high boiling point solvent.

[0019] Another aspect of the present invention provides a method for manufacturing a joint body, wherein the joint body comprises a first component, a second component, and a sintered copper column connecting the first component and the second component, and the method for manufacturing the joint body comprises: a step of molding the copper paste of the above aspect into a columnar shape on the first component, mounting the second component, and setting a column precursor between the first component and the second component; and a step of forming a sintered copper column by sintering the column precursor.

[0020] According to the method for producing a bonded body of the above aspect, a delay time of about 1 to 3 hours can be set from the formation of the column precursor to the mounting of the bonding member, so that the bonded body can be produced simply and stably.

[0021] Effects of the Invention

[0022] According to the present invention, its purpose is to provide a copper paste for forming a sintered copper column, and a method for manufacturing a joint body using the copper paste. When the copper paste for forming a sintered copper column is placed for a long time and then a joint component is mounted and sintered, a joint body joined by a sintered copper column can be stably formed. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic cross-sectional view showing one embodiment of the bonded body according to the present invention.

[0024] Figure 2 This is a schematic cross-sectional view for explaining one embodiment of a method for producing a bonded body according to the present invention.

[0025] Figure 3 This is a schematic cross-sectional view for explaining one embodiment of a method for producing a bonded body according to the present invention.

[0026] Figure 4 This is a schematic cross-sectional view for explaining one embodiment of a method for producing a bonded body according to the present invention.

[0027] Figure 5 This is a schematic cross-sectional view showing one embodiment of a component with a bonding post according to the present invention. DETAILED DESCRIPTION

[0028] Hereinafter, the mode for implementing the present invention is described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, its constituent elements (including essential steps, etc.) are not necessary except for the cases that are particularly clearly stated, the cases that are considered to be necessary and clear in principle, etc. The same is true about numerical values ​​and their ranges, and the present invention is not limited thereto.

[0029] In this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved. In this specification, the numerical range represented by "to" indicates a range that includes the numerical values ​​recorded before and after "to" as the minimum and maximum values, respectively. In this specification, regarding the content of each component in the composition, when there are multiple substances corresponding to each component in the composition, unless otherwise specified, it indicates the total amount of the multiple substances present in the composition. In this specification, "boiling point" refers to the boiling point under 1 atmosphere.

[0030] <Joint body>

[0031] Figure 1This is a schematic cross-sectional view for explaining one embodiment of the bonded body according to the present invention. Figure 1 The bonded body 10 shown includes a first member 1 , a second member 2 , and a sintered copper column 3 bonding the first member 1 and the second member 2 .

[0032] The lower surface and the upper surface of the sintered copper column respectively serve as the bonding surface with the first component and the bonding surface with the second component, and the two are bonded by metal bonding. By forming such metal bonding, the bonded body can be firmly bonded with low resistance.

[0033] Examples of the first component 1 and the second component 2 include active or passive electronic devices, wiring boards on which electronic devices are mounted, and packages having electronic devices and a rewiring layer provided on the electronic devices.

[0034] Examples of the electronic device include a coil, a capacitor, a SAW filter, a power IC, a logic chip, a memory chip, a sensor, a piezoelectric element, a transistor, and a diode.

[0035] Examples of the wiring board include mounting substrates, lead frames such as copper lead frames, ceramic substrates, resin molded products having printed metal wiring such as MID (Molded Interconnect Device), and packages having a rewiring layer.

[0036] One of the first component and the second component may be an active or passive electronic device, and the other may be a circuit board on which the electronic device is mounted. In this case, an electronic device with excellent reliability can be mounted.

[0037] Furthermore, both the first component and the second component may be a package including an electronic device and a rewiring layer provided on the electronic device, etc. In this case, a stacked package with excellent reliability can be mounted.

[0038] The first component and / or the second component may have one or more metals selected from the group consisting of copper, nickel, silver, platinum, gold and palladium on the bonding surface with the sintered copper column. These metals can reduce and remove the oxide film on the surface under a reducing atmosphere such as hydrogen or formic acid and at a sintering temperature below 300°C. Therefore, the joint body can have a high bonding strength by combining the exposed metal surface of the component with the metal of the sintered copper column. The above-mentioned metal can be provided on the first component and / or the second component as a metal film or a sintered metal layer.

[0039] The copper content in the sintered copper column is preferably 96% by mass or more, more preferably 96.5% by mass or more, and even more preferably 97% by mass or more, based on the total mass of the components constituting the sintered copper column (excluding carbon, oxygen, and nitrogen). In addition, the carbon, oxygen, and nitrogen are components that are sometimes randomly included in the sintered copper column by filling with an underfill agent or a sealing material based on mounting.

[0040] If the copper content in the sintered copper column is within the above range, it becomes easy to form the sintered copper column by printing and sintering the copper paste for forming the sintered copper column described later, and it is advantageous from the viewpoints of ensuring the bonding strength and suppressing electromigration. In addition, when the bonding surface contains copper, it is bonded by the same metal, so it is easy to suppress the generation of Kirschner voids, thereby achieving a bonded body with further excellent connection reliability.

[0041] From the viewpoint of thermal conductivity and electrical conductivity, the volume proportion of copper in the sintered copper column is preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 70% by volume or more. The larger the volume proportion of copper in the sintered copper column, the higher the thermal conductivity and electrical conductivity of the sintered copper column become, and thus it is preferred. In addition, in this specification, the portion other than copper of the sintered copper column is shown as a void. However, when a resin component such as a filling material or a bottom filler is contained in the void, the volume of the component is also included as the volume of the void. The volume proportion of copper in the sintered copper column can be obtained from the SEM image of the cross section of the sintered copper column.

[0042] The shortest distance H between the bonding surface of the sintered copper column with the first member and the bonding surface with the second member (sometimes also referred to as "height of the sintered copper column") may be 5 to 200 μm, 10 to 150 μm, or 20 to 100 μm.

[0043] The minimum diameter W of the sintered copper column in a cross section perpendicular to the direction in which the column extends (sometimes referred to as "width (diameter) of the sintered copper column") may be 10 to 500 μm, 25 to 300 μm, or 50 to 150 μm.

[0044] The ratio of H to W (H / W) in the sintered copper column (also referred to as "cross-sectional aspect ratio of the sintered copper column") may be 0.01 to 4.0, 0.1 to 2.5, or 0.15 to 2.0.

[0045] The above H and the above W can be obtained from a SEM image of a cross section of a sintered copper column.

[0046] In the joint body of the present embodiment, the shear strength between the joint surface of the first component and / or the second component and the sintered copper column can be set to be 4 MPa or more, 10 MPa or more, or 20 MPa or more. In this case, the joint surface of the first component and / or the second component can have the above-mentioned metal, or can have the above-mentioned metal as a metal layer.

[0047] The shear strength can be calculated, for example, by using a welding strength tester to push the sintered copper column horizontally at a constant speed with a tool of the device and dividing the maximum strength when the joint surface between the sintered copper column and the component is peeled by the cross-sectional area of ​​the column.

[0048] <Method for producing a bonded body>

[0049] The method for manufacturing a joint body of the present embodiment is a method for manufacturing the joint body involved in the present embodiment, and the method includes a step of forming a sintered copper column by sintering a column precursor disposed between a first component and a second component. The column precursor contains metal particles and an organic dispersion medium, and the metal particles can contain copper particles.

[0050] In this embodiment, after copper paste (copper paste for forming sintered copper pillars) is molded into a pillar shape on the first member by printing, for example, and then the second member is mounted, so that the pillar precursor can be provided between the first member and the second member.

[0051] [Copper paste for forming sintered copper pillars]

[0052] The copper paste for forming sintered copper posts according to the present embodiment contains metal particles and an organic dispersion medium, and the metal particles include copper particles.

[0053] Examples of the copper particles include submicron copper particles and micro copper particles. Submicron copper particles are copper particles having a particle size of 0.01 μm or more and less than 0.8 μm. Micro copper particles are copper particles having a particle size of 0.8 μm or more and 50 μm or less.

[0054] From the viewpoint of easily ensuring the bonding strength and connection reliability, the copper paste of the present embodiment preferably contains submicron copper particles. The copper paste may further contain micro copper particles and / or other metal particles other than copper particles as necessary.

[0055] (Submicron copper particles)

[0056] As submicron copper particles, copper particles having sinterability in a temperature range of 150°C to 300°C can be used. As submicron copper particles, copper particles having a particle size of 0.01 μm or more and less than 0.8 μm can be cited, for example, copper particles having a volume average particle size of 0.01 μm or more and less than 0.8 μm can be used. As long as the volume average particle size of the submicron copper particles is 0.01 μm or more, it is easy to obtain the effects of suppressing the synthesis cost of the submicron copper particles, good dispersibility, and suppressing the amount of surface treatment agent used. As long as the volume average particle size of the submicron copper particles is less than 0.8 μm, it is easy to obtain the effect of excellent sinterability of the submicron copper particles. From the viewpoint of further exerting the above-mentioned effects, the upper limit of the volume average particle size of the submicron copper particles can be 0.6 μm or less, 0.5 μm or less, or 0.4 μm or less. Furthermore, the lower limit of the volume average particle size of the submicron copper particles may be 0.02 μm or more, 0.05 μm or more, or 0.1 μm or more. The volume average particle size of the submicron copper particles may be, for example, 0.01 μm or more and 0.5 μm or less, 0.12 μm or more and less than 0.8 μm, 0.15 μm or more and less than 0.8 μm, 0.15 μm or more and 0.6 μm or less, 0.2 μm or more and 0.5 μm or less, or 0.3 μm or more and 0.45 μm or less.

[0057] In addition, in this specification, the volume average particle size refers to the 50% volume average particle size. When the volume average particle size of the copper particles is obtained, it can be obtained by the following method, etc., using a light scattering particle size distribution measuring device (for example, Shimadzu nanoparticle size distribution measuring device (SALD-7500nano, manufactured by Shimadzu Corporation)) to measure the copper particles used as the raw material for measurement, or the dry copper particles obtained by removing volatile components from the copper paste using a dispersant to disperse in a dispersion medium. When using a light scattering particle size distribution measuring device, hexane, toluene, α-terpineol, 4-methyl-1,3-dioxolane-2-one, etc. can be used as the dispersion medium.

[0058] The shape of the submicron copper particles is not particularly limited. The submicron copper particles may be, for example, spherical, blocky, needle-shaped, columnar, flaky or roughly spherical, or may be agglomerates of particles of these shapes. From the viewpoints of dispersibility and filling properties, the shape of the submicron copper particles may be spherical, roughly spherical or flaky, and from the viewpoints of flammability, dispersibility, and miscibility with flaky particles, the shape may be spherical or roughly spherical. In this specification, "flaky" includes flat plate shapes such as plate-like and scaly.

[0059] From the viewpoint of dispersibility, filling property and miscibility with flaky particles, the aspect ratio of the submicron copper particles may be 5 or less, 4 or less, or 3 or less. In this specification, "aspect ratio of a particle" (e.g., aspect ratio of a submicron copper particle) means the long side / thickness of a particle (e.g., a submicron copper particle). The long side and thickness of a particle can be determined, for example, from a SEM image of the particle.

[0060] Submicron copper particles can be treated with a specific surface treatment agent. Examples of specific surface treatment agents include organic acids having 2 to 18 carbon atoms (e.g., organic acids having an alkyl group having 1 to 17 carbon atoms). Examples of organic acids having 2 to 18 carbon atoms include acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, methylheptanoic acid, ethylhexanoic acid, propylpentanoic acid, nonanoic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, decanoic acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, lauric acid, methylundecanoic acid, ethyldecanoic acid, propylnonanoic acid, butylheptanoic acid, Octanoic acid, amyl heptanoic acid, tridecanoic acid, methyl dodecanoic acid, ethyl undecanoic acid, propyl decanoic acid, butyl nonanoic acid, amyl octanoic acid, myristic acid, methyl tridecanoic acid, ethyl dodecanoic acid, propyl undecanoic acid, butyl decanoic acid, amyl nonanoic acid, hexyl octanoic acid, pentadecanoic acid, methyl tetradecanoic acid, ethyl tridecanoic acid, propyl dodecanoic acid, butyl undecanoic acid, amyl decanoic acid, hexyl nonanoic acid, palmitic acid, methyl pentadecanoic acid, ethyl tetradecanoic acid, propyl Saturated fatty acids such as cyclohexane carboxylic acid, butyl cyclohexane carboxylic acid, pentyl undecanoic acid, hexadecanoic acid, heptyl nonanoic acid, heptadecanoic acid, octadecanoic acid, methyl cyclohexane carboxylic acid, ethyl cyclohexane carboxylic acid, propyl cyclohexane carboxylic acid, butyl cyclohexane carboxylic acid, pentyl cyclohexane carboxylic acid, hexyl cyclohexane carboxylic acid, heptyl cyclohexane carboxylic acid, octyl cyclohexane carboxylic acid, nonyl cyclohexane carboxylic acid; octenoic acid, nonenoic acid, methyl nonenoic acid, decenoic acid, undecenoic acid, dodecenoic acid Unsaturated fatty acids such as terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methylbenzoic acid, ethylbenzoic acid, propylbenzoic acid, butylbenzoic acid, pentylbenzoic acid, hexylbenzoic acid, heptylbenzoic acid, octylbenzoic acid and nonylbenzoic acid. The organic acid can be used alone or in combination of two or more. By combining this organic acid with the above-mentioned submicron copper particles, it is possible to take into account both the dispersibility of the submicron copper particles and the desorption of the organic acid during sintering.

[0061] The treatment amount of the surface treatment agent may be 0.07 mass % to 2.1 mass % inclusive, 0.10 mass % to 1.6 mass % inclusive, or 0.2 mass % to 1.1 mass % inclusive.

[0062] As submicron copper particles, commercially available products can be used. Examples of commercially available submicron copper particles include CH-0200 (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 0.36 μm), HT-14 (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 0.41 μm), CT-500 (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 0.72 μm), Tn-Cu100 (manufactured by TAIYO NIPPONSANSO CORPORATION, with a volume average particle size of 0.12 μm), and Cu-C-40 (manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., with a volume average particle size of 0.2 μm).

[0063] Based on the total mass of the metal particles, the content of the submicron copper particles can be more than 30 mass %, more than 40 mass %, more than 50 mass % or more than 60 mass %, or less than 100 mass %, less than 95 mass %, less than 90 mass % or less than 80 mass %. Based on the total mass of the metal particles, the content of the submicron copper particles can be more than 30 mass % and less than 100 mass %, can be more than 40 mass % and less than 90 mass %, can be more than 50 mass % and less than 95 mass %, can be more than 50 mass % and less than 80 mass %, can be more than 60 mass % and less than 80 mass %, or can be more than 60 mass % and less than 90 mass %. As long as the content of the submicron copper particles is within the above range, it is easy to ensure the bonding strength of the joint body obtained by sintering the column precursor formed by the copper paste, and when the parts of the joint body are micro devices, the micro devices tend to show good chip shear strength and connection reliability.

[0064] From the viewpoint of promoting sintering, achieving good connection between the first component and the second component, and demonstrating low-temperature sintering properties, the content of submicron copper particles can be greater than 20 mass % and less than 95 mass %, greater than 30 mass % and less than 85 mass %, or greater than 40 mass % and less than 75 mass %, based on the total amount of copper paste.

[0065] (Micro copper particles)

[0066] As the copper microparticles, copper particles having a particle diameter of 0.8 μm or more and 50 μm or less can be used. For example, copper particles having a volume average particle diameter of 0.8 μm or more and 50 μm or less can be used.

[0067] The micro copper particles are preferably combined with submicro copper particles for blending. In this case, the volume shrinkage and the generation of voids during sintering of the column precursor formed by the copper paste can be reduced, and it is easy to ensure the bonding strength of the joint body obtained by sintering the column precursor formed by the copper paste. When the part of the joint body is a micro device, the micro device tends to show good chip shear strength and connection reliability. From the viewpoint of further exerting the above-mentioned effects, the volume average particle size of the micro copper particles can be 0.8 μm or more and 20 μm or less, 0.8 μm or more and 10 μm or less, 2 μm or more and 10 μm or less, 3 μm or more and 20 μm or less, or 3 μm or more and 10 μm or less.

[0068] The shape of the copper microparticles is not particularly limited. The copper microparticles may be, for example, spherical, blocky, needle-shaped, flake-shaped, or substantially spherical, or may be aggregates of particles of these shapes.

[0069] In this embodiment, the flaky micro copper particles can be combined with the submicro copper particles. In this case, the micro copper particles in the column precursor are oriented approximately parallel to the bonding surface, which can suppress the volume shrinkage in the bonding surface direction when the column precursor is sintered, and it is easy to ensure the bonding strength of the joint obtained by sintering the column precursor. When the component of the joint is a micro device, the micro device tends to show good chip shear strength and connection reliability. From the viewpoint of further exerting the above-mentioned effect, the aspect ratio of the flaky micro copper particles is preferably 3 or more, more preferably 4 or more, and more preferably 6 or more.

[0070] In the micro-copper particles, there is no particular limitation on whether or not the surface treatment agent is used. From the viewpoint of dispersion stability and antioxidant properties, the micro-copper particles can be treated with a surface treatment agent. The surface treatment agent is removed during bonding. As such a surface treatment agent, for example, aliphatic carboxylic acids such as dodecanoic acid, palmitic acid, heptadecanoic acid, fatty acids, arachidic acid, linoleic acid, linoleic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, isobornyl cyclohexanol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanoonitrile; silane coupling agents such as alkyl alkoxysilanes; polymer treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, and silicone oligomers, etc. The surface treatment agent can be used alone or in combination of two or more.

[0071] Commercially available copper particles can be used. Examples of commercially available flaky copper particles include MA-C025KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 7.5 μm), 4L3N (manufactured by FUKUDA METALFOIL & POWDER Co., Ltd., with a volume average particle size of 3.0 μm), 3L3N (manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., with a volume average particle size of 5.7 μm), 3L3 (manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., with a volume average particle size of 8.0 μm), 2L3N (manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., with a volume average particle size of 9.9 μm), 1110F (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 3.8 μm), 1050YP (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 3.8 μm), and 1110YP (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 3.8 μm). Co., Ltd., with a volume average particle size of 0.94 μm), 1100YP (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 1.2 μm), 1200YP (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 3.4 μm) and 1400YP (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 5.2 μm).

[0072] Examples of spherical or substantially spherical micro-copper particles include 1050Y (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 0.81 μm), 1100Y (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 1.1 μm), 1200Y (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 2.1 μm), 1300Y (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 4.6 μm), 1400Y (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 5.5 μm), 1200YM (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 1.9 μm), 1300YM (manufactured by Mitsui Mining & Smelting Co., Ltd., with a volume average particle size of 2.1 μm), Co., Ltd., volume average particle size 3.4μm), 1400YM (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 4.2μm), Cu-HWQ 1.5μm (manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., volume average particle size 1.5μm), Cu-HWQ 1.5μm (manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., volume average particle size 1.4μm), Cu-HWQ 3.0μm (manufactured by FUKUDA METAL FOIL & POWDER Co., Ltd., volume average particle size 3.0μm), Cu-HWQ 5.0μm (manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., volume average particle size 4.1μm) and Cu-HWQ 10 μm (manufactured by FUKUDAMET AL FOIL & POWDER Co., Ltd., volume average particle size 9.4 μm).

[0073] Based on the total mass of the metal particles, the content of the micro-copper particles can be 0% by mass or more, more than 0% by mass, 5% by mass or more, or 10% by mass or more, or 70% by mass or less, 50% by mass or less, or 40% by mass or less. Based on the total mass of the metal particles, the content of the micro-copper particles is preferably 0% by mass or more and 70% by mass or less, more preferably more than 0% by mass or less and 70% by mass or less, further preferably 5% by mass or more and 50% by mass or less, and particularly preferably 10% by mass or more and 40% by mass or less.

[0074] In the copper paste of the present embodiment, based on the total mass of the metal particles, micro copper particles having a volume average particle size of 0.8 μm to 50 μm can be included at a ratio of more than 0% by mass and less than 50% by mass, preferably micro copper particles having a volume average particle size of 2 μm to 50 μm. In this case, the volume shrinkage and the generation of voids when the copper paste is sintered into a columnar shape can be reduced, and the bonding strength of the joint body bonded by the sintered copper column can be easily ensured.

[0075] When the flaky copper particles are blended, from the viewpoint of effectively obtaining the above-mentioned effects, the content of the flaky copper particles is preferably 0% by mass or more and 70% by mass or less, more preferably 5% by mass or more and 50% by mass or less, and further preferably 10% by mass or more and 40% by mass or less, based on the total mass of the metal particles, and is particularly preferably 20% by mass or more and 40% by mass or less, from the viewpoint of suppressing the deviation in the height of the column precursor and sufficiently ensuring the strength of the sintered copper column to further suppress the occurrence of cracks.

[0076] The copper paste of the present embodiment can contain copper nanoparticles within a range that does not impair the effects based on the above-mentioned micro copper particles and submicro copper particles. The copper nanoparticles are actually copper particles with a particle size of less than 0.01 μm. From the viewpoint of making the sintered copper column denser and increasing the copper content, the content of the copper nanoparticles is preferably 30% by mass or less, more preferably 15% by mass or less, further preferably 5% by mass or less, particularly preferably 1% by mass or less, and extremely preferably 0% by mass, i.e., no copper nanoparticles are contained, based on the total mass of the metal particles.

[0077] (Metal particles other than copper particles)

[0078] The metal particles may include other metal particles other than copper particles such as submicron copper particles and micro copper particles, for example, particles such as zinc, nickel, silver, gold, palladium, and platinum may be included. The volume average particle size of other metal particles other than copper particles may be 0.01 μm or more and 10 μm or less, 0.01 μm or more and 5 μm or less, or 0.05 μm or more and 3 μm or less. When the metal particles include other metal particles, from the perspective of obtaining sufficient bonding properties, the content of other metal particles may be less than 20% by mass, 10% or less by mass, 5% or less by mass, or 1% or less by mass based on the total mass of the metal particles. The metal particles may not include other metal particles. The shape of other metal particles is not particularly limited.

[0079] Based on the total mass of the metal particles, the content of other metal particles can be more than 1% by mass, or more than 5% by mass. When the copper paste contains metal particles other than copper particles, especially when it contains metal particles of metal species with low melting points, the sintering temperature can be reduced. In addition, a sintered body in which a plurality of metals are solid-dissolved or dispersed can be obtained, thereby improving the mechanical properties such as the yield stress and fatigue strength of the sintered body, and easily improving the connection reliability. Moreover, by adding a plurality of metal particles, the sintered body can have sufficient bonding strength relative to a specific bonded body. When the parts of the bonded body are micro devices, it is easy to improve the chip shear strength and connection reliability of the micro devices.

[0080] (Organic dispersion medium)

[0081] The organic dispersion medium includes a solvent having a boiling point of less than 280°C (hereinafter, also referred to as a "low boiling point solvent"). And a solvent having a boiling point of more than 280°C (hereinafter, also referred to as a "high boiling point solvent".). In the present embodiment, the content of the high boiling point solvent is 50 to 99% by mass based on the total mass of the organic dispersion medium. By using such an organic dispersion medium, when the bonding component is mounted and sintered after the column precursor is placed for a long time, a bonded body bonded with a sintered copper column can also be stably formed. The reason for obtaining such an effect is not clear, but the inventors speculate that the type and amount of the organic dispersion medium in the column precursor have an impact on the stable formation of the sintered copper column. That is, it is believed that in the present invention, the amount of the high boiling point solvent contained in the column precursor is not easy to change between the formation of the column precursor and the mounting of the bonding component, and the adhesion and flexibility are maintained by a certain amount of the high boiling point solvent remaining in the column precursor, and as a result, the above-mentioned effect is obtained. In addition, appropriate fluidity is obtained by the low boiling point solvent, so it is easy to shape the copper paste into a columnar shape.

[0082] From the viewpoint of forming columns more efficiently and with higher precision, the low boiling point solvent is preferably a solvent having a boiling point of 270° C. or less, more preferably a solvent having a boiling point of 260° C. or less, and still more preferably a solvent having a boiling point of 250° C. or less. The boiling point of the low boiling point solvent is, for example, 200° C. or more.

[0083] As the low boiling point solvent, α-terpineol, diethylene glycol monobutyl ether, diethylene glycol monobutyl ether acetate, 4-methyl-1,3-dioxolane-2-one, dihydroterpineol, etc. can be mentioned. Before sintering the column precursor, the low boiling point solvent can be easily removed in the drying process or the heating process. Among these, α-terpineol and dihydroterpineol are also preferred from the viewpoint that the column can be formed more effectively and with higher accuracy in combination with the high boiling point solvent described later. The low boiling point solvent can be used alone or in combination of multiple types.

[0084] As a high boiling point solvent, a solvent with a boiling point of 290°C or more is preferred, and a solvent with a boiling point of 300°C or more is more preferred. Since a dispersion medium with such a boiling point is easy to remain in the column precursor until the sintering temperature, that is, 150°C to 300°C, it is easier to maintain adhesion and flexibility. In addition, by using a dispersion medium with such a boiling point, it tends to be possible to further extend the placement time (the time from the formation of the column precursor to the mounting of the bonding component) for stably forming a joint body based on the sintered copper column. On the other hand, as a solvent with a boiling point of 280°C or more, a solvent with a boiling point of 450°C or less is preferred, and a solvent with a boiling point of 400°C or less is more preferred. Even at a temperature below the boiling point, the solvent will be volatilized and removed by its vapor pressure, but in a solvent with a boiling point exceeding 450°C, even at a sintering temperature of 150°C to 300°C, the volatilization rate becomes too slow, and it is easy to produce residual solvents that hinder sintering.

[0085] As a high boiling point solvent, in order to improve the dispersibility of the contained metal particles (for example, copper particles such as submicron copper particles and micro copper particles), it is preferred to select a solvent having a structure with high affinity to the surface of the metal particles. For example, when the metal particles are surface-treated with a surface treatment agent containing an alkyl group, it is preferred to select a solvent having an alkyl group. As a combination of a surface treatment agent and a high boiling point solvent for metal particles, it is preferred that the surface treatment agent is an organic acid containing an alkyl group having 1 to 17 carbon atoms, and the high boiling point solvent is a solvent containing an alkyl group having 1 to 17 carbon atoms. It is more preferred that the surface treatment agent is an organic acid containing an alkyl group having 5 to 17 carbon atoms, and the high boiling point solvent is a solvent containing an alkyl group having 5 to 17 carbon atoms. It is further preferred that the surface treatment agent is an organic acid containing an alkyl group having 10 to 17 carbon atoms, and the high boiling point solvent is a solvent containing an alkyl group having 10 to 17 carbon atoms. According to the above combination, when the content of the high boiling point solvent is increased, the metal particles can also be well dispersed.

[0086] Specific examples of the high boiling point solvent include isobornylcyclohexanol (MTPH, manufactured by NIPPON TERPENE CHEMICALS, INC.), butyl stearate, EXEPARL BS (manufactured by Kao Corporation), fatty acid fatty esters, EXEPARL SS (manufactured by Kao Corporation), fatty acid 2-ethylhexyl ester, EXEPARL EH-S (manufactured by Kao Corporation), fatty acid isotridecyl ester, EXEPARL TD-S (manufactured by Kao Corporation), isostearyl ester, FINEOXOCOL 180 (manufactured by Nissan Chemical Corporation), FINEOXOCOL 180T (manufactured by Nissan Chemical Corporation), 2-hexyldecanol, FINEOXOCOL 1600 (manufactured by Nissan Chemical Corporation), and FINEOXOCOL 180T (manufactured by Nissan Chemical Corporation). cal Corporation), tributyrin, tetraethylene glycol, heptadecane, octadecane, nonadecane, eicosane, heneicosane, docosane, methyl heptadecane, tridecylcyclohexane, tetradecylcyclohexane, pentadecylcyclohexane, hexadecylcyclohexane, undecylbenzene, dodecylphenyl, tetradecylbenzene, tridecylbenzene, pentadecylbenzene, hexadecylbenzene, heptadecylbenzene, nonylnaphthalenesulfonic acid, diphenylpropane, octyl octanoate, methyl myristate, ethyl myristate, methyl linoleate, fatty acid methyl ester, triethylene glycol bis(2-ethylhexanoic acid), tributyl citrate, amylphenol, dibutyl sebacate, oleyl alcohol, cetyl alcohol, methoxyphenylethanol, benzylphenol, hexadecanenitrile, heptadecanonitrile, benzyl benzoate, cyproconazole, etc. Among these, isobornyl cyclohexanol, isotridecyl fatty acid ester, octyl octyl, 2-ethylhexyl fatty acid and butyl stearate are preferred, and isobornyl cyclohexanol, octyl octyl and butyl stearate are particularly preferred, and isobornyl cyclohexanol and butyl stearate are further preferred. One high boiling point solvent can be used alone or in combination. When two or more high boiling point solvents are used in combination, for example, compared with a high boiling point solvent (isobornyl cyclohexanol, butyl stearate, etc.) with a relatively high viscosity, the solvent with high viscosity is diluted by other solvents through the combination of solvents, so the viscosity of the paste is reduced, and the release and coating performance of the paste are improved. In addition, when butyl stearate (freezing point of about 25°C) is used as one of the two or more high boiling point solvents, the freezing point tends to decrease, preventing the solidification of the paste. In particular, isobornyl cyclohexanol is preferably used in combination with tributyrin. In addition, butyl stearate is preferably used in combination with octyl octyl.

[0087] The content of the high boiling point solvent is 50% by mass or more based on the total mass of the organic dispersion medium, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more, from the viewpoint that it is not easy to volatilize from the column precursor and is easy to remain in the column precursor until sintering. The content of the high boiling point solvent is 99% by mass or less based on the total mass of the organic dispersion medium, preferably 98% by mass or less, and more preferably 97.5% by mass or less, from the viewpoint that the copper paste can be easily molded into a columnar shape with high precision by printing.

[0088] When isobornylcyclohexanol is used as the high boiling point solvent, the content of isobornylcyclohexanol may be 10% by mass or more, 15% by mass or more, or 30% by mass or less, or 50% by mass or less, 45% by mass or less, or 30% by mass or less, based on the total mass of the organic dispersion medium. The content of isobornylcyclohexanol may be 10 to 50% by mass, 15 to 45% by mass, or 20 to 30% by mass, based on the total mass of the organic dispersion medium.

[0089] When butyl stearate is used as a high boiling point solvent, from the viewpoint of improving the dispersibility of copper particles and the viewpoint that it is easy to remain in the column precursor until sintering, the content of butyl stearate can be 20% by mass or more, 30% by mass or more, or 40% by mass or more, based on the mass of the organic dispersion medium. From the viewpoint that the copper paste is easily formed into a columnar shape with high precision by printing, the content of butyl stearate can be 70% by mass or less, 60% by mass or less, or 55% by mass or less, based on the mass of the organic dispersion medium. From these viewpoints, the content of butyl stearate can be 20-70% by mass, 30-60% by mass, or 40-55% by mass, based on the mass of the organic dispersion medium.

[0090] Based on the total mass of the copper paste, the content of the high boiling point solvent is preferably 5% by mass or more, more preferably 7% by mass or more, and further preferably 8% by mass or more. In this case, the amount of the high boiling point solvent in the column precursor tends to become sufficient, and a stable column is easily formed. Based on the total mass of the copper paste, the content of the high boiling point solvent is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less. In this case, it tends to be easy to shape the copper paste into a columnar shape with high precision by printing. From these viewpoints, based on the total mass of the copper paste, the content of the high boiling point solvent is preferably 5-30% by mass, more preferably 7-25% by mass, and further preferably 8-20% by mass.

[0091] The content of the organic dispersion medium may be 5 to 50 parts by mass relative to 100 parts by mass of the metal particles. When the content of the organic dispersion medium is within the above range, the copper paste can be adjusted to a more appropriate viscosity and the sintering of the copper particles is less likely to be inhibited.

[0092] The type of organic dispersion medium contained in the copper paste can be analyzed, for example, by gas chromatography-mass spectrometry of high temperature desorption gas and TOF-SIMS. As other analytical methods, a method of confirming the supernatant obtained by centrifugation separation of particle components using conventional organic analysis (e.g., FT-IR, NMR, liquid chromatography, and a combination of these) can be cited. The ratio of the types of organic dispersion medium can be quantified by liquid chromatography, NMR, etc.

[0093] (Flexibility-imparting component)

[0094] The copper paste of this embodiment can contain a flexibility-imparting component. As the flexibility-imparting component, a thermally decomposable resin can be mentioned.

[0095] From the viewpoint of temporarily fixing the adherend and the column precursor after the formation of the column precursor until the sintering, the thermally decomposable resin is preferably a non-crystalline polymer that can exhibit adhesiveness or tackiness. Furthermore, the thermally decomposable resin preferably has both thermal decomposition properties that can decompose at the sintering temperature and can decompose without residue.

[0096] The thermal decomposition temperature of the thermally decomposable resin is preferably 300° C. or less, more preferably 250° C. or less. The thermal decomposition temperature of the thermally decomposable resin refers to the decomposition start temperature of the thermally decomposable resin, and is set to the 5% weight loss temperature in TG / DTA measurement. However, this temperature is not the decomposition start temperature in an oxidizing atmosphere such as air, but in a reducing atmosphere containing hydrogen, formic acid, etc. or an inert gas atmosphere from which oxygen is removed.

[0097] Since the residue after the thermal decomposition of the pyrolyzable resin hinders the sintering of the copper particles, the less the better. The amount of the residue after the thermal decomposition of the pyrolyzable resin is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less relative to the total mass of the resin before the thermal decomposition. The amount of the residue after the thermal decomposition of the pyrolyzable resin can be measured as the weight change after the sintering temperature is maintained only for the sintering time by TG / DTA of the pyrolyzable resin in an inert gas (nitrogen or argon) containing 3 to 5% by mass of hydrogen. In addition, since the TG / DTA measurement in the air performs oxidative decomposition, the amount of residue is less than that in a reducing atmosphere, so it is not preferred.

[0098] The thermally decomposable resin preferably has solubility in the organic dispersion medium. Examples of the thermally decomposable resin having solubility in the organic dispersion medium and the above-mentioned desired properties include polycarbonate, polymethacrylic acid, polymethacrylate, and polyester.

[0099] Based on the total mass of the copper paste, the content of the pyrolyzable resin in the copper paste may be 25% by mass or less, 15% by mass or less, 5% by mass or less, or 3% by mass or less. If the purpose is to form a sintered copper column, the pyrolyzable resin may not be added. On the other hand, from the perspective of increasing the proportion of the flexibility-imparting component contained in the total solvent to reduce the drying progress, based on the total mass of the copper paste, the content of the pyrolyzable resin in the copper paste may be 5% by mass or more.

[0100] The copper paste for forming the copper pillar of the present embodiment can be adjusted to a viscosity suitable for the printing / coating method for forming the pillar precursor. The viscosity of the copper paste at 25°C can be 50 Pa·s or more and 2000 Pa·s or less, 100 Pa·s or more and 1750 Pa·s or less, or 200 Pa·s or more and 1500 Pa·s or less. When the viscosity of the copper paste is within the above range, it is easy to form the pillar precursor by various printing methods described later.

[0101] In this specification, the viscosity of the copper paste for forming sintered copper columns refers to the value measured by an E-type viscometer at 25°C and a rotation speed of 0.5 rpm. As the E-type viscometer, for example, a viscometer manufactured by Toki Sangyo Co., Ltd., product name: VISCOMETER-TV33 can be used. As a measuring fixture for a conical rotor, for example, 3°×R14, SPP can be applied.

[0102] The thixotropic index (hereinafter also referred to as TI value) of the copper paste for forming sintered copper pillars of the present embodiment may be 2.0 to 20, 3.0 to 15, or 4.0 to 10. If the TI value of the copper paste is within this range, the viscosity of the copper paste is reduced by shear force, so that the printing is facilitated by manual operation or stirring with a stirring device (for example, a self-rotating and revolving stirring device (Planetary Vacuum Mixer ARV-310, manufactured by THINKY CORPORATION)) before printing, and the viscosity of the copper paste is restored by standing after it is attached to the member to be adhered, thereby suppressing excessive wetting and spreading of the printed matter.

[0103] In this specification, the TI value is defined as the viscosity μm measured at 25°C and 0.5 rpm using an E-type viscometer. 0.5, when the viscosity measured at 25°C and a rotation speed of 5 rpm is μ5, the value calculated using the following formula.

[0104] TI value = μ 0.5 / μ5

[0105] [Method for preparing copper paste]

[0106] Copper paste can be prepared by mixing the above-mentioned copper particles, organic dispersion medium, and other metal particles and any additives with flexibility as needed. For example, it can be prepared by dispersing the flexibility-imparting component after dissolving it in an organic solvent, adding submicron copper particles, micro copper particles, other metal particles and any additives for dispersion treatment. Alternatively, it can be prepared by mixing the flexibility-imparting component and dissolving it in a solution of an organic solvent, mixing the copper particles in a solvent and dispersing the dispersion, other metal particles and any additives. In addition, when the dispersibility of the high boiling point solvent and the metal particles is insufficient, the copper paste can be prepared by adding and mixing the high boiling point solvent after the metal particles are dispersed in a low boiling point solvent. When the combination of the surface treatment agent of the metal particles and the high boiling point solvent is the above-mentioned preferred combination, this operation is not required, so that a metal paste containing more high boiling point solvents can be prepared more effectively.

[0107] When the copper particles include submicron copper particles and micro copper particles, a dispersant can be added to an organic solvent or a flexibility imparting component as needed, and a dispersion treatment is first carried out on the basis of mixing the submicron copper particles, and then other metal particles are added to the micro copper particles as needed for dispersion treatment. The dispersion method and dispersion conditions suitable for submicron copper particles and micro copper particles are sometimes different from each other. Generally, in submicron copper particles, a stronger dispersion than that of micro copper particles is required. On the other hand, micro copper particles are easily dispersed and are sufficient under low-intensity dispersion, and micro copper particles are deformed under strong dispersion. By setting the above steps, the dispersibility becomes good, and the performance of the copper paste can be further improved. It is also possible to remove the agglomerate by performing a classification operation on the dispersion liquid.

[0108] In the present preparation method, stirring treatment can be performed after mixing the components. The maximum particle size of the copper paste dispersion can be adjusted by classification operation. At this time, the maximum particle size of the dispersion can be set to 20 μm or less, and can also be set to 10 μm or less.

[0109] The dispersion treatment can be carried out using a disperser or a stirrer, for example, an Ishikawa-type stirrer, a SILVERS ON stirrer, a cavitation stirrer, a rotation-revolution stirring device, an ultra-thin film high-speed rotary disperser, an ultrasonic disperser, a pounding machine, a twin-screw kneading machine, a bead mill, a ball mill, a three-roll mill, a homogenizer, a planetary mixer, an ultra-high pressure disperser, a thin-layer shear disperser, etc.

[0110] The stirring treatment can be performed using a stirrer, for example, an Ishikawa mixer, a self-rotating and revolving stirring device, a pounder, a twin-screw kneader, a three-roll mill, a planetary mixer, etc.

[0111] The classification operation can be performed, for example, by filtration, natural sedimentation, centrifugal separation, etc. Examples of the filter for filtration include a wide-tooth comb, a metal mesh, a metal filter, and a nylon mesh.

[0112] [Formation of column precursor]

[0113] In the method of this embodiment, after copper paste (copper paste for forming sintered copper pillars) is molded into a pillar shape by printing on the first member, the second member is mounted, so that the pillar precursor can be provided between the first member and the second member.

[0114] As the printing method of copper paste, for example, screen printing, transfer printing, offset printing, jet printing, a dispenser, a jet dispenser, a needle dispenser, a comma coater, a slit coater, a die coater, a gravure coater, a slit coating method, relief printing, gravure printing, gravure printing, stencil printing, soft hole plate printing, rod coating, application, particle accumulation method, spray coater, spin coater, dip coater, electrodeposition coating, etc. can be used.

[0115] From the viewpoints of simple manufacturing process, easy to maintain shape stability, and easy thick film printing, it is preferred to form the copper paste into a columnar shape by screen printing or stencil printing. In this case, for example, a metal mask 4 ( Figure 2 (a)), then, the copper paste 3a is extended using a scraper 5, and the copper paste 3a is filled in the hole portion of the metal mask 4 ( Figure 2 Thus, a copper paste 3b (molded into a columnar shape) is provided on the first component 1. Figure 3 (a)).

[0116] The guide hole diameter of the metal mask used for screen printing or stencil printing can be 30 μm or more and 200 μm or more, or 50 μm or more and 100 μm or less. The holes can be arranged in a grid pattern, and the pitch interval can be 1 μm or more and 500 μm or less. The scraper angle can be 10° or more and 90° or less, or 45° or more and 70° or less.

[0117] The printing height H1 may be 5 μm or more and 500 μm or less, or 10 μm or more and 200 μm or less. Furthermore, the wetting spread W1 from the end of the column after printing may be 100 μm or less, or 50 μm or less.

[0118] The pressing depth (H1-H2) when mounting the second member 2 may be 500 μm or less, 100 μm or less, or 50 μm or less from the top of the copper paste formed into a column. H2 is set in consideration of the height of the sintered copper column or column precursor to be formed.

[0119] For example, when the first component and the second component are a micro device and a substrate, the second component can be mounted using a chip mounter, a flip chip bonder, or a positioning jig made of carbon or ceramics.

[0120] Thus, the column precursor 3c ( Figure 3 (b)).

[0121] Next, the column precursor 3c disposed between the first member 1 and the second member 2 is sintered to form a sintered copper column 3, thereby obtaining a joint body 10 ( Figure 3 (c)).

[0122] From the viewpoint of suppressing the flow during sintering and the generation of voids, the column precursor can also be properly dried. The gas atmosphere during drying can be in the air, in an oxygen-free atmosphere such as nitrogen and rare gases, or in a reducing atmosphere such as hydrogen and formic acid. The drying method can be drying by placing at room temperature, can be heating drying, or can be reduced pressure drying. When heating drying or reduced pressure drying, for example, a heating plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, a hot plate stamping device, etc. can be used. The drying temperature and time can be appropriately adjusted according to the type and amount of the organic dispersion medium and the flexibility imparting component used. As the drying temperature and time, for example, it can be set to more than 50°C and less than 180°C, and more than 30 seconds and less than 120 minutes.

[0123] The sintering of the column precursor can be performed by heat treatment, for example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, etc. can be used for the heat treatment.

[0124] From the viewpoint of removing the copper particles contained in the column precursor and the surface oxide of the bonded surface, the gas atmosphere during sintering may be a reducing atmosphere. Examples of the reducing atmosphere include pure hydrogen, a mixed gas of hydrogen and nitrogen represented by a synthetic gas, nitrogen containing formic acid gas, a mixed gas of hydrogen and a rare gas, and a rare gas containing formic acid gas.

[0125] In this embodiment, the diameter of the column precursor is small (especially, when it is less than 200 μm), and the formic acid enters the interior of the column precursor, so the copper particles are easily reduced, and the copper particles can be fully sintered in the reducing atmosphere containing formic acid gas. In this case, the sintering can be performed using a formic acid reflow furnace, which can effectively improve the degree of sintering.

[0126] From the viewpoint of fully performing sintering, reducing thermal damage to components such as micro devices and substrates, and improving yield, the maximum temperature reached during the heat treatment may be 150° C. or higher and 300° C. or lower, 170° C. or higher and 250° C. or higher and 200° C. or lower. As long as the maximum temperature reached is 150° C. or higher, sintering tends to be fully performed even if the maximum temperature holding time is 60 minutes or less.

[0127] From the perspective of being able to fully remove the organic dispersion medium and flexibility-imparting components, fully perform sintering, and improve the yield, the holding time at the maximum temperature can be from 1 minute to 60 minutes, from 1 minute to less than 40 minutes, or from 1 minute to less than 30 minutes.

[0128] The method for manufacturing a joint body of the present embodiment may further include a step of filling a resin around the sintered copper column. In this case, a joint body 20 ( Figure 4 ).

[0129] As the sealing material, from the viewpoint of protecting the joint portion from heat, moisture and impact and further improving the connection reliability, a compression molding sealing material, a liquid sealing material, a transfer molding sealing material, an underfill sealing material, etc. can be used.

[0130] <Parts with joint posts>

[0131] The component with bonding columns of the present embodiment is, for example, a component having a metal layer and a column arranged on the metal layer, and is bonded to other components via the column, wherein the column is composed of sintered copper, and the copper content in the column is greater than 96% by mass based on the total mass of the components constituting the column (excluding carbon, oxygen and nitrogen), and the volume ratio of copper in the column is greater than 50% by volume.

[0132] Figure 5 This is a schematic cross-sectional view showing one embodiment of a component with a bonding post. Figure 5 The member 30 with joining posts shown includes a first member 1 and posts 3d provided on the first member 1. The member 30 with joining posts is joined to a second member.

[0133] The component 30 with the bonding column is manufactured in the same manner as the manufacturing method of the bonded body of the present embodiment described above ( Figure 3 (a)) is obtained by sintering the copper paste formed into a columnar shape until it is formed into a columnar shape on the first component.

[0134] The selection of components, preparation of copper paste, molding and sintering of the copper paste can be performed in the same manner as in the method for producing a joint body according to the present embodiment described above, and the preferred conditions are also the same.

[0135] Compared with electrolytic plating, the bonding column composed of sintered copper and having the above structure can be formed in a shorter time, has excellent thermal conductivity and electrical conductivity, and is not prone to electromigration. According to the component with bonding columns having such columns, it is easy to ensure the connection reliability of the bonded body obtained by bonding to other components, and the manufacturing process of the bonded body can be shortened.

[0136] When the component with the bonding pillar of the present embodiment is bonded to other components via the pillar, copper paste can be used. In this case, the same type of sintered copper bonding pillars are used, so that the electromigration resistance is improved, the Kirschner voids are suppressed, the thermal conductivity is improved, and the data transmission characteristics are improved, and as a result, a mounting body with excellent connection reliability and electrical characteristics can be obtained. The above copper paste can be set to the same structure as the copper paste for forming the sintered copper pillar of the present embodiment.

[0137] Example

[0138] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0139] (Example 1)

[0140] The copper paste was prepared, the bonded body was produced and evaluated, and the component with bonding posts was produced and evaluated by the following method.

[0141] [Preparation of copper paste]

[0142] In an agate mortar were added 0.058 g of α-terpineol (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.), 0.256 g of tributyrin (dispersion medium), a mixture of a slurry of CH-0200 (submicron copper particles, a product name manufactured by Mitsui Mining & Smelting Co., Ltd., 50% volume average particle size: 0.36 μm, surface treatment agent: lauric acid) and α-terpineol (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.) (CH-200:α-terpineol=91:9, mass ratio) 2.189 g, 3L3N (flaky micro copper particles, a product name manufactured by FUKUDA METAL FOIL & POWDER Co., Ltd., volume average particle size: 5.7 μm) 0.493 g, and zinc (other metal particles, Alfa Aesar, Inc., product number: 13789) 0.006 g was mixed until there was no dry powder, and the mixture was transferred to a plastic bottle.

[0143] The sealed plastic bottles were stirred at 2000 min using a rotation and revolution stirring device (Planetary Vacuum Mixer ARV-310, manufactured by THINKY CORPORATION). -1 The mixture was stirred at 2000 rpm for 2 minutes.

[0144] [Production of a joint body]

[0145] The copper paste 1 was used to form a bonded body by the following method. On a copper plate (15 mm, thickness 0.3 mm) as the first component, A stainless steel metal mask (784 openings per 7 mm, thickness: 50 μm) was used to form a grid with openings spaced 250 μm apart, and copper paste was applied by template printing using a metal scraper. After applying the copper paste, it was left at room temperature for a specified time, and a Si chip (3 mm, thickness 0.15 mm) with Ni plating as the second component was mounted on the columnar copper paste provided on the substrate, and a press-in fixture with Spencer was used to press 10 μm from the top of the Si chip. The specified time was set to 1 hour, 2 hours and 3 hours. Afterwards, these stacked bodies (copper plate / column precursor / Si chip) were placed in a hydrogen sintering furnace (hydrogen 100% reducing atmosphere), and the temperature was raised to 225°C at a heating rate of 7.5°C / min, and maintained at 225°C for 60 minutes. Afterwards, the samples were cooled to 200°C over 5 minutes, kept at 200°C for 5 minutes, and quenched to room temperature to obtain joint body 1 (with Si chip mounted on it after standing for 1 hour), joint body 2 (with Si chip mounted on it after standing for 2 hours), and joint body 3 (with Si chip mounted on it after standing for 3 hours).

[0146] [Evaluation of the joint state 1]

[0147] The bonded bodies 1 to 3 were turned inside out and slightly vibrated to perform a simple evaluation of the bondability, and the bonded state was evaluated according to the following criteria. The results are shown in Table 1.

[0148] [Judgment criteria]

[0149] A: The Si chips of the bonded bodies 1 to 3 were not peeled off and were present on the copper substrate.

[0150] B: The Si chips of the bonded bodies 1 and 2 were not peeled off, but the Si chip of the bonded body 3 was peeled off.

[0151] C: The Si chip of the bonded body 1 was not peeled off, but the Si chips of the bonded bodies 2 and 3 were peeled off.

[0152] D: The Si chips of all the bonded bodies 1 to 3 were peeled off.

[0153] [Evaluation of bonding status 2]

[0154] The conjugate obtained in the above-mentioned Evaluation 1 was added to the cup, fixed with a sample clamp (Samplklip I, manufactured by Buehl er Co.), and epoxy injection molding resin (product name "Epomount", manufactured by Re fine Tec Ltd.) was poured around it until the entire conjugate was filled, and allowed to stand in a vacuum chamber and decompressed for 1 minute to defoam.

[0155] After that, the epoxy injection molding resin was cured at room temperature (25°C) for 10 hours to obtain an injection molding sample. Using Refineso Excel (manufactured by Refine Tec Ltd.) with a thermosetting resin cutting wheel, the injection molding sample was cut near the cross section to be observed. Next, the cross section was cut using a polishing device (Refine Polisher HV, manufactured by Refine Tec Ltd.) with water-resistant polishing paper (carbon fiber paper, manufactured by Refine Tec Ltd.) to expose the joint of the sintered copper column. In addition, an ion milling device "IM4000" (manufactured by Hitachi, Ltd.) was used, and the end exposed from the mask was cut in CP mode to make a sample for observation.

[0156] The cross section of the bonded portion in the observation sample was observed at various magnifications with an applied voltage of 15 kV. It was confirmed that the sintered copper column was metal-bonded to the bonded body in the bonded body where the Si chip was not peeled off.

[0157] (Examples 2 and 3)

[0158] Copper pastes 2 and 3 were obtained in the same manner as in Example 1 except that the blending amount of each component was adjusted so that the content of each component became the value shown in Table 1. A joint body was prepared and evaluated in the same manner as in Example 1 except that the obtained copper paste 2 or 3 was used. The results are shown in Table 1.

[0159] (Examples 4 and 5)

[0160] Copper pastes 4 and 5 were obtained in the same manner as in Example 1, except that isobornyl cyclohexanol (Terusolve MTPH, manufactured by NIPPON TERPEN ECHEMICALS, INC.) was used as a dispersion medium and the blending amount of each component was adjusted so that the content of each component became the value shown in Table 1. Except for using the obtained copper paste 4 or 5, the preparation and evaluation of the joint body were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0161] (Example 6)

[0162] In an agate mortar, 0.1772 g of octyl octanoate (dispersion medium, manufactured by Sigma-Aldrich Japan), 2.0308 g of a slurry mixture of CH-0200 (submicron copper particles, manufactured by Mitsui Mining & Smelting Co., Ltd., product name, 50% volume average particle size: 0.36 μm), α-terpineol (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.) and butyl stearate (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.) (CH-200: α-terpineol: butyl stearate = 91:0.9:8.1, mass ratio), 0.7867 g of 3L3N (flaky micro copper particles, manufactured by FUKUDAMETAL FOIL & POWDER Co., Ltd., product name, volume average particle size: 5.7 μm), and zinc (other metal particles, Alfa Aesar, Inc., product number: 13789) 0.006 g was mixed until there was no dry powder, and the mixed solution was transferred to a plastic bottle.

[0163] The sealed plastic bottles were stirred at 2000 min using a rotation and revolution stirring device (Planetary Vacuum Mixer ARV-310, manufactured by THINKY CORPORATION). -1 The mixture was stirred at 2000 rpm for 2 minutes. Thus, copper paste 6 was obtained. A joint body was prepared and evaluated in the same manner as in Example 1 except that the obtained copper paste 6 was used. The results are shown in Table 1.

[0164] (Examples 7 to 11)

[0165] Copper pastes 7 to 11 were obtained in the same manner as in Example 6 except that the blending amount of each component was adjusted so that the content of each component became the value shown in Table 2. Except for using the obtained copper pastes 7 to 11, joints were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0166] (Comparative Examples 1 to 3)

[0167] Copper pastes 12 to 14 were obtained in the same manner as in Example 1, except that the blending amount of each component was adjusted so that the content of each component became the value shown in Table 3. In addition, the α-terpineol used in Comparative Example 2 was only the α-terpineol contained in the slurry mixture, and no additional α-terpineol was added during kneading. Except for using the obtained copper pastes 12 to 14, the preparation and evaluation of the joint body were carried out in the same manner as in Example 1. The results are shown in Table 3.

[0168]

[0169]

[0170]

[0171] Explanation of symbols

[0172] 1-first component, 2-second component, 3-sintered copper column, 3a-copper paste, 4-metal mask, 5-scraper, 10, 20-joined body, 30-component with joining column.

Claims

1. A copper paste for forming a sintered copper column, which is used to form a sintered copper column for bonding components to each other, the copper paste containing metal particles and an organic dispersion medium, The metal particles include copper particles, The organic dispersion medium contains 50 to 99 mass % of a high boiling point solvent having a boiling point of 280° C. or higher, based on the total mass of the organic dispersion medium.

2. The copper paste according to claim 1, wherein Based on the total mass of the copper paste, the content of the high boiling point solvent is 5 to 30 mass %.

3. The copper paste according to claim 1 or 2, wherein: The organic dispersion medium contains two or more of the high boiling point solvents.

4. The copper paste according to any one of claims 1 to 3, wherein The high boiling point solvent includes at least one selected from the group consisting of isobornylcyclohexanol and butyl stearate.

5. A method for manufacturing a bonded body, the bonded body comprising a first component, a second component, and a sintered copper column that bonds the first component and the second component, the method comprising: A step of molding the copper paste according to any one of claims 1 to 4 into a columnar shape on the first component, mounting the second component, and providing a column precursor between the first component and the second component; and The step of forming the sintered copper column by sintering the column precursor.

Citation Information

Patent Citations

  • Method for electrical coupling and electric coupling arrangement

    US20160351529A1

Cited By

  • Ultrathin metal welding layer preparation method based on distributed interval coating and silver soldering paste

    CN120940763A